Considerations on Liver Injuries Caused by CPR Case Presentation - Ioan, Beatrice; Hanganu, Bianca; Neagu, Marius (The Bulletin of Legal Medicine, 2015)
Cardiac arrest is a life-threatening condition which requires fast maneuvers for saving the victim’s life. Cardio-pulmonary resuscitation (CPR) is one of the easiest and handiest maneuver which proved many times to be savior even though sometimes it could worsen the victim’s prognosis. In this paper the authors present the case of a 75-year old male, with a significant medical history and long term thrombolytic treatment who suffered a witnessed cardiac arrest. The emergency team who arrived at the victim’s home initiated the CPR and transported him to the hospital. The electrocardiogram showed inferior-lateral acute myocardial infarction and the cardiologist in the emergency room decided to transfer him to another hospital for specialized treatment. Despite the fact that the CPR was continued in the ambulance in order to maintain the cardiac activity, the blood pressure decreased gradually and he died couple of hours later. Internal examination at the autospy revealed multiple injuries caused by the cardiac massage: rib and sternum fractures, massive intraperitoneal bleeding, liver laceration and contusion. This paper brings to the attention of the physicians the issue of the iatrogenic injuries following the CPR and the possibility for these injuries to contribute to thanatogenesis. The authors also analyze the factors influencing the quality of the life-saving procedures and the role of the pathologist in establishing the correct cause of death taking into the gravity of the CPR related injuries.Keywords: CPR, liver injury, death
Keywords: cpr; liver injury; death